Penanganan Lonjakan Vibrasi pada Rotor Elektrik Turbin di PLTU Gresik - abdul ghofar romdhon; Mohammad Ilham; rini puji astutik; denny irawan (Indonesian Society of Applied Science (ISAS), 2020)
This analysis will discuss how to handle vibrations in the Turbine Rotor. The measuring instrument used is Vibration Analysis test with Prov. 2140 type which measured amplitude, time and frequency domain of vibration signal. The results obtained in this study, firstly, the measurement vibration of rotor at PT PJB Gresik found the highest amplitude of vibration was 59,6 μm at 3000 rpm. In this condition, the rotor is in very good condition as per standard vibration in ISO 7919-2 stated 80 μm at 3000 rpm. However in the next measurement, there is an dramatically increase of amplitude in each vibration measurement. The top amplitude of vibration reached at 115 μm at 3000 rpm and shown a symtom of damage on the rotor as a result of vibration. In solving the problem this time we use the method Root couse analysis (RCA). The results of this research found that there was a short turn to turn on the rotor windings and the closed slot liner holes that caused electric vibrations and needed to be repaired to eliminate vibration disturbances. After repairing the vibration, it decreased which initially 115 μm to 33.5 μm at 3000 Rpm, it is still on the range of the permitted safe zone of ISO standard 7919−2.